IRRI/CCAFS approach on community-based seed systems is adopted in other projects in Laos - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The CSA approach targeting rice seed systems in Phailom have been adopted by an FAO/ IUCN project on a RAMSAR site in Southern Laos. Moreover, the work has led to a proposal on strengthening rice seed systems under migration-driven feminization of agriculture in Laos. This clearly indicates the growing interest towards improved seed systems in Lao PDR which can also be seen in the number of farmers interested to join Farmers' Field School.